Disk brake design for cooling improvement using Computational Fluid Dynamics (CFD) - Munisamy K.M.; Shafik R. (Institute of Physics Publishing, 2023)
The car disk brake design is improved with two different blade designs compared to the baseline blade design. The two designs were simulated in Computational fluid dynamics (CFD) to obtain heat transfer properties such as Nusselt number and Heat transfer coefficient. The heat transfer property is compared against the baseline design. The improved shape has the highest heat transfer performance. The curved design is inferior to baseline design in heat transfer performance. Published under licence by IOP Publishing Ltd.